THE EFFECT OF EARNING PER SHARE (EPS), RETURN ON EQUITY (ROE), AND DEBT TO EQUITY RATIO (DER) ON STOCK PRICES OF LQ45 COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FROM 2015 TO 2022 (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the effect of Earning Per Share (EPS), Return On Equity (ROE), and Debt to Equity Ratio (DER) on stock prices of LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the period 2015 to 2022. The research employs a quantitative method with an associative approach. The sample consists of 14 companies selected using purposive sampling. Data were collected through literature studies and analyzed using multiple linear regression. The results show that partially, EPS has a negative and significant effect on stock prices, ROE has a negative but not significant effect, and DER has a negative and significant effect on stock prices. Simultaneously, EPS, ROE, and DER have a positive and significant effect on stock prices.